Congenital cytomegalovirus infection – diagnosis dilemma - Gołkowska, Małgorzata; Dobrzańska, Anna (Przewodnik Lekarza/Guide for GPs, 2008)
Congenital cytomegalovirus infection is the most common viral infection in newborns. It is a leading cause of damage of the central nervous system in children, specially hearing loss, visual defects and mental retardation. Congenital cytomegalovirus infection is an invisible, still rarely diagnosed disease. Awareness is low and treatment is very expensive. Diagnosis of congenital cytomegalovirus infection is often difficult. Only 10–15% of newborns present symptoms after birth. In 85–90% of newborns there are no signs of disease after birth. Commonly used serologic tests are not adequate to make an appropriate diagnosis. They need to be confirmed with molecular methods. Antiviral treatment of congenital cytomegalovirus infection is reserved for symptomatic HCMV infection. The decision about antiviral treatment should be made taking into consideration possible side effects of the treatment.